Criterias of the Quality of Primary Education - Onakhon Jabborova; Gulhayo Torayeva (Euro Asian Journal Publishing, 2024)
The article analyzes the quality criteria of primary education and presents the individual approach of the authors
Keywords: Primary education; quality of education; criteria and approaches